Relationships between algal primary productivity and environmental variables in tropical floodplain wetlands. Issue 2 (3rd April 2021) - Molinari, Bianca; Stewart-Koster, Ben; Adame, Maria Fernanda; Campbell, Max D.; McGregor, Glenn; Schulz, Cameron; Malthus, Tim J.; Bunn, Stuart
ABSTRACT: Floodplain wetlands are among the most productive and biodiverse ecosystems on Earth and provide a major subsidy of food resources for consumers in river systems. The basal energy source for those consumers in many systems comes from aquatic algal production influenced by different characteristics of the floodplain environment. Our aim was to estimate relationships between algal productivity and environmental variables in the channels and wetlands of the Mitchell River floodplain in tropical Australia. We measured physical, chemical, and biological variables in a range of different wetland types (palustrine, lacustrine, and riverine) and different habitat types (emergent macrophytes, floating macrophytes, submerged macrophytes, and open water). The most productive areas were found among riverine wetlands and submerged habitats. The statistical models showed that habitat type and turbidity alone can predict algal productivity with reasonable accuracy (pseudo- R 2  = 0.35, n  = 63). Importantly, those attributes can be measured using remote sensing, and hence the model can be used to predict algal productivity over wider spatial scales and identify important "hotspot" areas of primary productivity that sustain aquatic food webs. Through this approach we can inform current conservation and water planning frameworks to manage the impact of human development on the productivity of wetlands at large spatial scales.